Anti-α-glucosidase and anti-oxidative isoflavonoids from the immature fruits of Maclura tricuspidata. (February 2022) - Jo, Yang Hee; Lee, Solip; Yeon, Sang Won; Ryu, Se Hwan; Turk, Ayman; Hwang, Bang Yeon; Han, Yoo Kyong; Lee, Ki Yong; Lee, Mi Kyeong
Abstract: The composition of a plant, together with its efficacy, vary depending on its maturity and plant parts. In this study, the chemical constituents of immature fruits of Maclura tricuspidata (Moraceae) were investigated together with their anti-diabetic and antioxidant effects. A total of 34 compounds were isolated from the immature fruits of M. tricuspidata using various chromatographic methods. Structure elucidation using extensive spectroscopic analysis led to the characterization of isolated compounds as isoflavonoids with prenyl substituents. Among them, macluraisoflavones A-O were first isolated from nature. The anti-diabetic and antioxidant activity of the isolated compounds were also suggested by α-glucosidase inhibitory activity and DPPH radical scavenging activity, respectively. In particular, macluraisoflavone I, an isoflavonoid with 2, 2-dimethylpyran and 2-hydroperoxy-3-methylbut-3-enyl moieties, showed potent α-glucosidase inhibitory activity and DPPH radical scavenging activity. Further molecular docking analysis suggested hydrogen bond and alkyl interactions between α-glucosidase and macluraisoflavone I. Therefore, the immature fruits of M. tricuspidata can be used as an important natural product with antioxidant and anti-diabetic properties. Graphical abstract: Fifteen undescribed isoflavonoids, macluraisoflavones A-O, and 19 known compounds were isolated from the immature fruits of Maclura tricuspidata, which showed anti-α-glucosidase and anti-oxidative activity. Image 1 Highlights: Thirty-four compounds were isolated from the immature fruits of Maclura tricuspidata . They were isoflavonoid with different numbers and types of prenyl moieties. Fifteen compounds, macluraisoflavones A-O, were undescribed. Macluraisoflavone I showed α-glucosidase inhibitory and antioxidant activity. The interaction with α-glucosidase was analyzed by molecular docking analysis.